Reformulation of Indonesian Human Rights Courts Competence in the Context of Ius Constituendum - Aditya Wiguna Sanjaya (Universitas Muhammadiyah Sidoarjo, 2019)
Crime of aggression and war crimes are not regulated in the competence of Human Rights Courts in Indonesia, in this case indicates that in positive law of Indonesia especially Act Number 26 of 2000 indicates the existence of legal issues which is legal vacuum on that matter needed solution through academic study as the purpose of this research. The methodology used in this research is a normative juridical research method that is focused on studying the application of rules or norms in positive law. In the study of normative jurisprudence, activities to elaborate the law are not required data support or social facts, because normative legal science does not recognize data or social facts, only known for legal material, so to explain the law or to find meaning and give value of the law is only used the concept of law and the steps taken are normative steps. The results of this study indicate that the Indonesian Human Rights Court has not been able to work independently because there is still influence from outside tribunal which is the International Criminal Court.